Prevalence & Consequences of Anaemia in Pregnancy - Dayal, Sheetal; Dayal, Achleshwar (International Journal of Medical Research and Review, 2014)
Introduction: This study is planned with aim to identify prevalence of anaemia in specified population in south India and to know various adverse consequences of anaemia in mother and child. Methods: This is a prospective observational study done in pregnant women indicates anaemia in pregnancy is a risk factor for low birth weight(LBW), preterm delivery, poor APGAR score and possibly early neonatal death. Results: After comparison with non anaemic and anaemic group we fond that there is 2.5 to 3.5 times increase in LBW, preterm delivery and early neonatal death in anaemic group. WHO criteria is used for classification of anaemia and we found 60% of our study population are anaemic. Conclusion: This study conform the recommendations of various previous studies that anaemia is strongly associated with LBW, preterm delivery and early neonatal death.